THE EFFECT OF WORK MOTIVATION AND THE WORK ENVIRONMENT ON WORK PRODUCTIVITY IN THE POLYTECHNIC OF LP3I JAKARTA KAMPUS KRAMAT RAYA - D. Purnomo; Siti Fatimah (Jurnal Inovasi Penelitian, 2021)
The aim of the study is to find out the effect of motivation through the employee productivity, the effect of work environment to the employee productivity, the effect of motivation and work environment simultaneously through the productivity of Politeknik LP3I Jakarta Kramat Raya Campus employees. This research was conducted from March to September 2018, the research used an explanatory research which was also correlational, the survey method used by the researcher is a questionnaire method. The respondents are Politeknik LP3I Jakarta Kramat Raya Campus employees. The participants of the study are 50 people, based on Arikunto’s formula if the population is less than 100 people, then the total sample is as whole taken. Data analysis was carried out descriptively and used causal hypotheses test. The result of Hypothesis Test showed that motivation and work enviroment influenced through the work froductivity. And also based on the result of SPSS test whowed that hypothesis (1) t score = 4.850 is greater than t table of 2.012 and significant of 0,000 is smaller than 0,05, therefore H0 is rejected and H1 is accepted. It means that motivation influences to to the work productivity of the employees. Hypothesis (2) t score = 3.247 is greater than t table of 2.012 and significant of 0.000 is smaller than 0.05, therefore H0 is rejected and H1 is accepted. It means that work environment influencs through Employee productivity. Hypothesis (3) F score = 11.186 is greater than F table of 3.20 and significant of 0.000 is smaller than 0.05, therefore H0 is rejected and H1 is accepted. It means that work motivation influences through work productivity of the employees.